DEGRADATION DETERMINATION OF TINOSORB-S IN SUNSCREEN PREPARATIONS - Jana, Kallol; Mahanti, Beduin (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The main objective was to determine the Tinosorb-S degradation in the sunscreen preparations with a simple economic linear and specific analytical method. Methods: The RP-HPLC was achieved with 100% methyl alcohol as the mobile phase, a flow rate of 2.5 mL/min., and an octadecylsilane column (300 × 3.9 cm, 10 µ) at 254 nm. Results: The developed analytical method of Tinosorb-S was statistically validated for accuracy and linearity of 70–130 µg/mL. The correlation coefficient was 0.996, and the % RSD of precision was 0.957. The recovery percentage was 100.01–105.04, and the excellent thermal and photolytic stability of Tinosorb-S was confirmed by the thermal, dry, and wet chromatograms compared with the standard; no such degradation was developed, and the recovery was 99.52%, 99.44%, and 99.45%, respectively. Acid, oxidative, and alkaline decomposition of Tinosorb-S were established by screening the decomposition peaks, and the percentage recovery was 41.31%, 40.38%, and 40.44%, respectively. Conclusions: The stress degradation study of Tinosorb-S is important in stability to evaluate the maximum protecting power of skin from harmful UV rays. Conditions like photolytic degradation, exposure to thermal conditions, acid hydrolysis, oxidation, and alkali hydrolysis were studied with a cost-effective, specific, linear, high-performance liquid chromatographic method with a photodiode array detector.